2023
DOI: 10.3389/fimmu.2023.1121795
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-AIFM2-1 promotes HBV immune escape by acting as a ceRNA for miR-330-3p to regulate CD244 expression

Abstract: Chronic hepatitis B (CHB) virus infection is a major risk factor for cirrhosis and hepatocellular carcinoma (HCC). Hepatitis B virus (HBV) immune escape is regulated by the exhaustion of virus-specific CD8+ T cells, which is associated with abnormal expression of negative regulatory molecule CD244. However, the underlying mechanisms are unclear. To investigate the important roles of non-coding RNAs play in CD244 regulating HBV immune escape, we performed microarray analysis to determine the differential expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…MiR-330-3p has been acknowledged for its suppressive effects on various human tumors, including colorectal cancer, melanoma, and ovarian cancer (21)(22)(23). Notably, miR-330-3p downregulation ampli es HCC cell proliferation (24,25). In line with the previous studies, miR-330-3p expression was decreased in both HCC cell lines and tissues.…”
Section: Discussionsupporting
confidence: 81%
“…MiR-330-3p has been acknowledged for its suppressive effects on various human tumors, including colorectal cancer, melanoma, and ovarian cancer (21)(22)(23). Notably, miR-330-3p downregulation ampli es HCC cell proliferation (24,25). In line with the previous studies, miR-330-3p expression was decreased in both HCC cell lines and tissues.…”
Section: Discussionsupporting
confidence: 81%
“…These findings suggest that the expression of CD244 may play an independent role in the chronicity of HBV infection. It is now believed that the possible mechanism is that Lnc-AIFM2-1 acts as an endogenous competitive RNA (ceRNA) for miR-330-3p to regulate the expression of CD244 on CD8+ T cells and contributes to the immune escape of HBV [ 61 ]. Studies conducted at the epigenetic level have revealed that examining the gene regulation process in immune cells during HBV clearance can provide valuable insights into the expression of crucial genes that determine the function of immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…Jurkat cells were placed in the upper chamber of Transwell while LX-2 cells were placed in the lower chamber. This process was done to detect the impact of LX-2 cells on the apoptosis and proliferation of immune cells Jurkat [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…HBV immune escape plays a pivotal role in the development of liver cirrhosis, impeding the ability of the immune system to eliminate the HBV virus, thus leading to persistent infection [ 10 ]. This not only heightens the risk of patients developing cirrhosis and liver cancer, but also complicates treatment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation